Resveratrol synthesis under natural conditions and after UV-C irradiation in berry skin is associated with berry development stages in 'Beihong' (V. vinifera × V. amurensis). (1st February 2015) - Wang, Jun-Fang; Ma, Ling; Xi, Hui-Fen; Wang, Li-Jun; Li, Shao-Hua
Highlights: Under natural conditions, res synthesis during berry development was related to veraison. UV-C could significantly stimulate the synthesis of res, mainly in the form of trans -res. Res synthesis at two weeks before veraison was the most sensitive to UV-C. Abstract: Though UV-C irradiation may induce the synthesis of resveratrol in grape berry skins, it is unclear which developmental stage is most sensitive to UV-C induction. In this study, we investigated resveratrol content and gene expression of 'Beihong' ( Vitis vinifera × Vitis amurensis ) berries by UV-C irradiation compared with under natural conditions during different developmental stages. Under natural condition, resveratrol synthesis was related to veraison. Before veraison, resveratrol content was very low; however, total resveratrol increased about 500% from veraison to maturity in the main forms of piceids. UV-C irradiation significantly stimulated resveratrol synthesis, mainly in the form of trans -resveratrol. Young berries at 55 days after anthesis were most sensitive to UV-C irradiation, the total resveratrol in the skin of UV-C irradiated berry is about 90 times higher than that of the control; however, resveratrol synthesis subsequently declined, which may be attributed to STS regulation by Myb14 .